2005
DOI: 10.1016/j.femsec.2005.02.008
|View full text |Cite
|
Sign up to set email alerts
|

RpoS involvement and requirement for exogenous nutrient for osmotically induced cross protection in Vibrio vulnificus

Abstract: Vibrio vulnificus is an opportunistic human pathogen which is the causative agent of food-borne disease and wound infections. V. vulnificus is able to adapt to a variety of potentially stressful environmental changes, such as osmotic, nutrient, and temperature variations in estuarine environments, as well as oxidative, osmotic, and acidity differences following infection of a human host. After exposure to sub-lethal levels of a particular environmental stress, many bacteria become resistant to unrelated stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
6
32
0
Order By: Relevance
“…These results indicate that salinity and temperature tolerance mechanisms may be coupled at the molecular level, consistent with the findings of previous studies demonstrating that pre-exposure to osmotic stress increased the tolerance to heat stress in V. vulnificus (Rosche et al, 2005). Such coupling may result from temperature and salinity responses using common molecular pathways such as the SOS response pathway, the heat-shock response pathway and the general stress response pathway (Hengge-Aronis, 2002;Diez-Gonzalez and Kuruc, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicate that salinity and temperature tolerance mechanisms may be coupled at the molecular level, consistent with the findings of previous studies demonstrating that pre-exposure to osmotic stress increased the tolerance to heat stress in V. vulnificus (Rosche et al, 2005). Such coupling may result from temperature and salinity responses using common molecular pathways such as the SOS response pathway, the heat-shock response pathway and the general stress response pathway (Hengge-Aronis, 2002;Diez-Gonzalez and Kuruc, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Such coupling may result from temperature and salinity responses using common molecular pathways such as the SOS response pathway, the heat-shock response pathway and the general stress response pathway (Hengge-Aronis, 2002;Diez-Gonzalez and Kuruc, 2009). However, Rosche et al (2005) have demonstrated that the cross-protection between osmolarity and heat in V. vulnificus is independent of rpoS, the master regulator of the general stress response mechanism, and were unable to elucidate the origin of this cross-protection. An alternative potential mechanism for coupling between stress responses is partitioning of cellular resources between different stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to a slightly acidic pH prior to low-pH exposure dramatically increases survival of this organism, demonstrating the induction of a stress response(s) which provides a protective effect for the subsequent stresses (127). While there are limited data on protection against acid stress in this organism, nutrient starvation has been shown to induce cross-protective effects against oxidative stress (130). Furthermore, cross-protection following starvation has been shown to increase survival of this pathogen under both clinical and environmental conditions (9,130).…”
Section: Host Resistancementioning
confidence: 99%
“…While there are limited data on protection against acid stress in this organism, nutrient starvation has been shown to induce cross-protective effects against oxidative stress (130). Furthermore, cross-protection following starvation has been shown to increase survival of this pathogen under both clinical and environmental conditions (9,130). These cross-protective abilities are likely an important contributor to the survival of this organism and may work in concert with the mechanisms outlined above to allow its survival as it passes through the gastric environment.…”
Section: Host Resistancementioning
confidence: 99%
“…The stress response sigma factor, RpoS, has been studied in V. cholerae, V. vulnificus, V. anguillarum, V. harveyi, and V. alginolyticus and has been shown to be involved in a number of stress responses in these species, including starvation, osmolarity, ethanol, hydrogen peroxide, and acid stress responses (11)(12)(13)(14)(15)(16)(17). Previously, RpoS was also studied in V. parahaemolyticus and was found to play a limited role in the stress response in this organism (10).…”
mentioning
confidence: 99%